2020
DOI: 10.1186/s42269-020-00384-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antioxidant and storability of Hollywood plum cultivar by preharvest treatments with moringa leaf extract and some nutrients

Abstract: Background Plum fruit has a short shelf life with a rapid deterioration in quality after harvest. The main aim of this study was to evaluate the effect of preharvest treatments by moringa leaf extract (MLE), boric acid (B), and chelated calcium (Ca EDTA) on Hollywood plum fruit quality attributes bioactive compounds and antioxidant activity during cold storage. Plum trees were sprayed twice: at full bloom stage and 1 month later with T1, 5% MLE + 1% B + 2% Ca EDTA; T2, 5% MLE + 2% B + 3% Ca EDTA; T3, 10% MLE +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…According to Thanaa et al [63], foliar spraying with 6% MLE resulted in higher lightness (L*) and hue angle (h • ) value of plum fruit, which was likely due to the increased enzyme activity and anthocyanin content by the MLE application, leading to the formation of more colored fruit. These results are in agreement with the findings by Mahmoud et al [61], who found an increase of L* in Hollywood plum cultivar.…”
Section: Color and Sensory Attributessupporting
confidence: 94%
See 1 more Smart Citation
“…According to Thanaa et al [63], foliar spraying with 6% MLE resulted in higher lightness (L*) and hue angle (h • ) value of plum fruit, which was likely due to the increased enzyme activity and anthocyanin content by the MLE application, leading to the formation of more colored fruit. These results are in agreement with the findings by Mahmoud et al [61], who found an increase of L* in Hollywood plum cultivar.…”
Section: Color and Sensory Attributessupporting
confidence: 94%
“…A similar conclusion was found by Abo El-Enien et al [60], i.e., foliar spraying of MLE significantly enhanced fruit firmness of the navel orange. The application of 10% MLE together with 2% B and 3% Ca improved the firmness of plum fruit [61]. Moreover, Ismail and Ganzour [22] reported an increment in fruit firmness of strawberries after spraying solely with MLE or in combination with KNO 3 .…”
Section: Firmnessmentioning
confidence: 99%
“…Total phenolic content (TPC, mg GAE/kg) continuously increased in the fruits treated with oils until 9 days from the start of the storage period, at which point the trend slowed down gradually and peaked on day 18. Mahmoud et al [73] found that the TPC of the Hollywood plum was increased during cold storage. Piljac-Žegarac and Šamec [74] reported that small fruits like strawberries, raspberries, cherries and sour cherries stored at 4 • C exhibited slightly higher antioxidant activity values.…”
Section: Fruit Visual and Chemical Parametersmentioning
confidence: 99%
“…Results on color attributes of fruit peels showed that plants treated with foliar MLE at 1:20 had higher L* values (37.54) compared to the control. Thanaa et al [61] and Mahmoud et al [62] found similar results when using pre-harvest MLE treatment on L* in plum fruit. Meanwhile, our study revealed that a* and b* values were negatively influenced by the treatments.…”
Section: Discussionmentioning
confidence: 60%